DEFEAT OF THE CARDIOVASCULAR SYSTEM IN VIRAL INFECTIONS - E. V. Sharipova; I. V. Babachenko; A. S. Levina (Журнал инфектологии, 2018)
Article is devoted to studying of the submitted epidemiological, clinical, tool, laboratory data on pathology of cardiovascular system at various viral infections. The review is based on results of domestic and foreign researches. At viral infections damage of heart and his carrying-out system perhaps as during the sharp period of a disease, and the period of a convalescence or at the chronic course of virus process. The greatest cardiothrogenism is possessed by enteroviruses, which affect the myocardium in 5–15% of cases. Much attention is paid to herpesviruses, widespread, persistently persistent in the body, as one of the reasons for the development of dilated cardiomyopathy, coronary vasculitis, early atherosclerosis, cardiac rhythm disturbance. Other infections that may affect the cardiovascular system include influenza viruses, adenovirus, poliovirus, Epstein-Barr virus, cytomegalovirus, human immunodeficiency virus, hepatitis, mumps, rubella, herpes simplex, varicella, arbovirus, respiratory-syntial virus, yellow fever virus et al. Complications from cardiovascular system can come to light at various age.